Effectiveness of Computer-Assisted Instruction and Conventional Instructional Approaches on High School Student Performance in Cellular Respiration - Ebenezer Ato Baiden; Samuel Agbene (MASI Mandiri Edukasi, 2022)
This study examined the effects of computer-aided instruction (CAI) and conventional teaching methods on high school biology performance. He was randomly selected from each of his two schools to take two science courses. An unequal, quasi-experimental, pre-test, and post-test design were used. Students in the experimental group used their CAI to learn cellular respiration (a biological concept), while the control group learned the same cellular respiration using a conventional approach. Independent and paired-samples t-tests were used to analyze pre-and post-test results for both experimental and control groups. Results showed that students taught using the traditional approach performed better on the post-test than those taught using the CAI. However, students in the experimental group performed better after being instructed to use the CAI. The results also showed that underperforming students performed better after being tutored at CAI. This indicates that CAI is more effective in teaching underperforming students.